Application of UAV for Village Mapping in Pangambatan, Sumatra Utara - Utami, Rahmi; Khair, Hafizhul; Rahayu, Silda; Lordye, Grace (Talenta Publisher, 2023)
Pangambatan Village, as part of the Lake Toba National Strategic Area and a tourist destination, still lacks facilities, infrastructure, and professional human resources to manage its cultural and tourism potential. An initial mapping of the conditions and potential of the area is needed to drive tourism in Pangambatan Village towards sustainable tourism. This can be done by mapping environmental conditions and tourism potential in Pangambatan Village, providing recommendations for sustainable tourism management, and providing environmental management facilities. The study was carried out using Unmanned Aerial Vehicle (UAV) technology. UAV technology offers new opportunities for fast and efficient remote environmental monitoring and the collection of high spatial and temporal resolution data. The benefits of this mapping can be used to see environmental conditions and environmental pollution that may occur because of tourist activities. In addition, the use of this technology is expected to help related parties in making decisions and planning.